Evolution in the management of soft tissue sarcoma: classification, surgery and use of radiotherapy. (30th April 2020) - Dei Tos, Angelo Paolo; Bonvalot, Sylvie; Haas, Rick
ABSTRACT: Background : Given the rapid evolution in the management of soft tissue sarcoma (STS), it is essential to revisit the evidence regularly. This review examines topics of interest for early management of STS: the impact of molecular genetics on sarcoma classification; the importance of a correct diagnosis and strategy in the surgical management of STS; current status on use of radiotherapy in STS. Areas covered : Accurate diagnosis of STS combines histomorphology, immunochemistry, and molecular genetics, although morphology is the mainstay of therapeutic planning. As diagnosis of STS is challenging, it is best conducted within a multidisciplinary environment. Expert surgery in STS takes into account multiple parameters including biopsy, imaging, pathological knowledge, technical issues, and a multidisciplinary approach. The sum of these factors informs decisions about whether or not to perform surgery and the choice of surgical technique. Advances in radiotherapy are challenging the paradigm of applying the same dose and treatment schedule to all STS patients irrespective of subtype. Preoperative radiotherapy of specific histotypes appears to be the future although more research is required to address uncertainties such as fraction size, total dose, combined modality regimens, and individual sensitivity to radiotherapy. Expert opinion : STS should be managed in a reference center.